PF277 ALICE: AN AML STUDY WITH LSD1 INHIBITION IN COMBINATION WITH AZACITIDINE IN THE ELDERLY - Montesinos, P.; Somervaille, T.; Salamero, O.; Gutierrez, S.; Xaus, J.; Buesa, C.; Maes, T.; Bullock, R. (HemaSphere, 2019)
Background: Acute Myeloid Leukaemia (AML) is primarily a disease of older people and its incidence is rising. Survival rates decrease with age as does the achievement of complete remission (CR) with current chemotherapy, for which there is no consensus for optimal re‐therapy. Azacitidine is approved for AML with 20–30% blasts. Lysine‐specific demethylase (LSD1) has been shown to be a partner in some gene transformations in AML and helps sustain the oncogenic process. Iadademstat (ORY‐1001) is a highly potent and selective LSD1 inhibitor that has been shown to be effective in preclinical models (both alone or in combination with other compounds, including Azacitidine); and remarkably safe in a phase I study, where it also demonstrated preliminary anti‐leukaemic activity as monotherapy. Iadademstat in combination with azacitidine may thus offer a novel treatment option for a patient group with limited current options. Aims: To assess safety, tolerability and dose finding of iadademstat in combination with azacitidine, and to measure the clinical activity such as time to response (TTR), duration of response (DOR) and objective response (OR) of this combination in older patients who are not eligible to be treated with intensive chemotherapy. Other assessments include haematological improvement and overall survival, along with PK/PD measures (including a set of 6 blood biomarkers). Methods: This is a two‐stage phase II multicentre open‐label study of safety, tolerability, dose‐finding and efficacy of iadademstat in combination with azacitidine in elderly patients. The dose finding stage will dose 12–18 patients with a starting dose of iadademstat of 90 μg/m2/d. Depending on the DLTs observed, iadademstat may be escalated or de‐escalated. Once the Recommended Phase II Dose (RP2D) is identified, an expansion cohort of 18 patients will be enrolled and treated with iadademstat combined with azacitidine. In all cases patients to be recruited correspond to subjects ≥ 60 years of age with AML according to World Health Organization (WHO) classification, who are considered by the investigator to be ineligible for intensive chemotherapy regimen at that time or have refused standard chemotherapy, and which may not have received prior treatment for AML other than Hydroxyurea. Results: The patient assessments of all the enrolled study subjects will be presented as per May 2019 cut‐off, with particular emphasis on available preliminary efficacy outcomes. Current recruitment rate suggests that the available data will include the safety data after the first‐cycle of treatment of the first 8–10 participants. Moreover, preliminary efficacy data of all subjects in any of the cycles will be also presented. Summary/Conclusion: This first combination Phase IIa study with iadademstat aims to further extend the safety and efficacy of iadademstat in the oncology field; in this case, in older unfit leukemic patients as a first line treatment, providing initial support for the effect of its holistic unique MoA, which has been recently related to the potentiation of several other approaches, including immune‐oncology therapies in solid tumors.